A second discovery of Lacertopontonia chadi Marin, 2011 (Crustacea: Decapoda: Palaemonidae), with remarks on its systematic position - Fransen, Charles H. J. M.; Reijnen, Bastian T. (Zootaxa, 2012)
A second discovery of the cockscomb oyster associated shrimp species Lacertopontonia chadi is recorded from Sabah (Malaysia). The material is compared with the type description and paratypic material. The systematic position of the genus is reevaluated on the basis of morphological and molecular data focusing on the genera Conchodytes and Chernocaris. It is concluded that Lacertopontonia and Chernocaris fall within the present definition of Conchodytes and should be regarded as synonyms of the latter.